2012
DOI: 10.1177/0148607112457422
|View full text |Cite
|
Sign up to set email alerts
|

Role of Peripherally Inserted Central Catheters in Home Parenteral Nutrition

Abstract: PICCs are similar in terms of catheter-related complications to other CVCs for the administration of HPN, especially for oncology patients with HPN lasting <6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 20 publications
0
33
2
1
Order By: Relevance
“…We typically do not recommend a single‐ or double‐lumen PICC line for HPN duration longer than 6 weeks. A recent prospective study of 72 patients receiving HPN reported 0 infections per 1000 catheter days for PICC lines, compared with 20 in Hickman catheters ( P = .07) 22 . In contrast to our study, however, that study had a disproportionate number of patients with a PICC line (67%) compared with Hickman catheters (14%).…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…We typically do not recommend a single‐ or double‐lumen PICC line for HPN duration longer than 6 weeks. A recent prospective study of 72 patients receiving HPN reported 0 infections per 1000 catheter days for PICC lines, compared with 20 in Hickman catheters ( P = .07) 22 . In contrast to our study, however, that study had a disproportionate number of patients with a PICC line (67%) compared with Hickman catheters (14%).…”
Section: Discussioncontrasting
confidence: 97%
“…In contrast to our study, however, that study had a disproportionate number of patients with a PICC line (67%) compared with Hickman catheters (14%). Furthermore, the underlying reason for HPN was cancer in >80% of patients in that cohort, compared with only 22.7% in our cohort 22 . That study's results 22 are in contrast to our data and those of a previous study that showed a significant increase in CRBSI for patients using PICCs for HPN compared with other central venous catheters 21 …”
Section: Discussioncontrasting
confidence: 90%
“…Another prospective study by the same research group, found a CRBSI rate of 0.35 per 1000 catheter days and 0.60 per 1000 HPN days [23]. Other studies have reported CRBSI rates ranging from 0.41 to 1.7 per 1000 catheter days [21, 22, 24, 25, 30]. We did not find any significant difference in the incidence of CRBSI across the three types of VAD, though it is to be noted that of a total of 408 VADs in this study, only 11 (2.7%) were TCCs.…”
Section: Discussionmentioning
confidence: 99%
“…Peripherally inserted central catheters are appropriate for HPN 62 but would likely not be the best choice for an athlete due to the location, the lack of a Dacron cuff in a patient prone to increased sweating, and soiling of the dressing.…”
Section: Assessment and Energy Requirements For The Athlete Receiving Pnmentioning
confidence: 99%